Haemostatic alterations induced by treatment with asparaginases and clinical consequences - Stefano, Valerio De; Za, Tommaso; Ciminello, Angela; Betti, Silvia; Rossi, Elena (Thrombosis and Haemostasis, 2015)
The benefit of asparaginase for treating acute lymphoid leukaemia (ALL) has been well established. Native asparaginase derives from Escherichia coli (colaspase) or Erwinia chrysanthemi (crisantaspase); in a third preparation, colaspase is pegylated. Depletion of asparagine leads to decreased synthesis of procoagulant, anticoagulant, and fibrinolytic proteins, with resultant hypercoagulability and greater risk of venous thromboembolism (VTE). Colaspase and crisantaspase are not dose-equivalent, with crisantaspase displaying haemostatic toxicity only at dosages much higher and administered more frequently than those of colaspase. Cerebral venous thrombosis and pulmonary embolism are two life-endangering manifestations that occur during treatment with asparaginase particularly in children and in adults with ALL, respectively. Approximately one-third of VTEs are located in the upper extremities and are central venous line-related. Other risk factors are longer duration of asparaginase treatment and concomitant use of prednisone, anthracyclines, and oral contraceptives. The risk associated with inherited thrombophilia is uncertain but is clearly enhanced by other risk factors or by the use of prednisone. VTE prevention with fresh frozen plasma is not recommended; the efficacy of antithrombin (AT) concentrates has occasionally been reported, but these reports should be confirmed by proper studies, and AT should not be routinely employed. Therapeutic or prophylactic heparin doses are only partially effective, and direct thrombin or factor Xa inhibitors could play significant roles in the near future.
Keywords: Asparaginase; hypercoagulability; thrombosis; antithrombin concentrate; heparin